Plant Morphology and Analysis of Yellow Temulawak Curcumin (Curcuma xanthorrhiza Roxb.) In the Kinilow Village - Meilani Elseday Ma'tan; Arthur G. Pinaria; James B. Kaligis; Jackson F. Watung; Frangky J. Paat; Diane D. Pioh (Sam Ratulangi University, 2022)
Temulawak or Curcuma xanthorrhiza Roxb is a very famous plant in Indonesia, even in the world. Temulawak is a plant that is often used as medicine and can be found in tropical forests. The purpose of this study was to determine the morphology of the yellow temulawak plant and to analyze the content of the curcumin compound found in the yellow temulawak. This study used TLC-Densitometry. The sample used was yellow curcuma found in Kinilow Village, Tomohon City, North Sulawesi Province. For morphological observations, only one plant was used as the object of observation. Based on the results of the study it can be concluded that the morphology of yellow temulawak has a plant height of 1.29 m, stem height of 79 cm, leaf length of 71 cm, leaf width of 26 cm. Curcuma is white, purple and light green. flowers, root length 13 cm, and rhizome weight 250 grams. The curcumin content of yellow temulawak was obtained at 0.98%. Keywords: Temulawak, curcumin, TLC-Densitometry Abstrak Temulawak atau Curcuma xanthorrhiza Roxb merupakan tumbuhan yang sangat terkenal di Indonesia, bahkan di dunia. Temulawak merupakan tanaman yang sering digunakan sebagai obat dan dapat ditemukan di hutan tropis. Tujuan dari penelitian ini adalah untuk mengetahui morfologi tanaman temulawak kuning dan menganalisis kandungan senyawa kurkumin yang terdapat pada temulawak kuning. Penelitian ini menggunakan KLT-Densitometri. Sampel yang digunakan adalah temulawak kuning yang terdapat di Desa Kinilow Kota Tomohon Provinsi Sulawesi Utara. Untuk pengamatan morfologi, hanya satu tumbuhan yang dijadikan objek pengamatan. Berdasarkan hasil penelitian dapat disimpulkan morfologi temulawak kuning memiliki tinggi tanaman 1,29 m, tinggi batang 79 cm, panjang daun 71 cm, lebar daun 26 cm. Temulawak berwarna putih, ungu dan hijau muda. bunga, panjang akar 13 cm, dan berat rimpang 250 gram. Kandungan kurkumin temulawak kuning diperoleh sebesar 0,98%. Kata kunci: Temulawak, kurkumin, KLT-Densitometri